الأدب الفلسطيني وسيلة لاسترداد حرية القدس : Palestinian Literature as a Mean of Recapturing the Freedom of al-Quds - Mohamad Zainol, Nur Farhana; Ahmad H. Osman, Rahmah (Journal of Al-Tamaddun, 2024)
This study aims to highlight the position and the role of the Palestinian literature in emphasizing the spirit of resistance and defiance for the sake of liberation of Jerusalem. The study relies on the analytical descriptive approach, which it analyses the content of several Palestinian poems which call to defend the land of Jerusalem. This study found that literature is a reflection of societies where it portrays the social realities of specific societies. And as Palestinian people witness a major political and social conflicts for more than fifty years up until now, hence some of them choose to express their experiences through literary writings. Therefore, this study concludes that Palestinian literature plays a very important role in proliferating the Palestinian issues to the people all around the world, encourages people to defend the land of Jerusalem and later on liberate it from the Israeli occupiers by any appropriate and suitable means.